Behavioral variation according to feeding organ diversification in glossiphoniid leeches (Phylum: Annelida) - Hee-Jin Kwak (Nature Portfolio, 2021)
Abstract Adaptive radiation is a phenomenon in which various organs are diversified morphologically or functionally as animals adapt to environmental inputs. Leeches exhibit a variety of ingestion behaviors and morphologically diverse ingestion organs. In this study, we investigated the correlation between behavioral pattern and feeding organ structure of leech species. Among them, we found that Alboglossiphonia sp. swallows prey whole using its proboscis, whereas other leeches exhibit typical fluid-sucking behavior. To address whether the different feeding behaviors are intrinsic, we investigated the behavioral patterns and muscle arrangements in the earlier developmental stage of glossiphoniid leeches. Juvenile Glossiphoniidae including the Alboglossiphonia sp. exhibit the fluid ingestion behavior and have the proboscis with the compartmentalized muscle layers. This study provides the characteristics of leeches with specific ingestion behaviors, and a comparison of structural differences that serves as the first evidence of the proboscis diversification.